2019
DOI: 10.1103/physrevapplied.12.014041
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Highly Asymmetric Magnetoelectric Effects in Engineered Multiferroic Heterostructures

Abstract: One of the main strategies to control magnetism by voltage is the use of magnetostrictive-piezoelectric hybrid materials, such as ferromagnetic-ferroelectric heterostructures. When such heterostructures are subjected to an electric field, piezostrain-mediated effects, electronic charging, and voltage-driven oxygen migration (magnetoionics) may simultaneously occur, making the interpretation of the magnetoelectric effects not straightforward and often leading to misconceptions. Typically, the strain-mediated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
(233 reference statements)
1
7
0
Order By: Relevance
“…3(b,c,d). The overall dependences of HC and MR/MS with voltage resemble those measured along the [100] direction on FeAl sputtered onto <110>-oriented PMN−32PT single crystals, ascribed to electric field-induced piezoelectric substrate deformation 13 . This is expectable since both FeAl and FeGa display similar magnetostrictive behavior 40 .…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…3(b,c,d). The overall dependences of HC and MR/MS with voltage resemble those measured along the [100] direction on FeAl sputtered onto <110>-oriented PMN−32PT single crystals, ascribed to electric field-induced piezoelectric substrate deformation 13 . This is expectable since both FeAl and FeGa display similar magnetostrictive behavior 40 .…”
mentioning
confidence: 61%
“…By replacing magnetic field actuation (through the use of miniaturized electromagnets) with electric fields (created by external voltage), it is possible to drastically reduce Joule heating effects, thereby minimizing electric power dissipation [1][2][3][4][5][6][7] . Converse magnetoelectric actuation has been shown to be an effective means to tune the coercivity, saturation magnetization or squareness ratio (i.e., effective magnetic anisotropy) of thin films, taking advantage of electric surface charging (or charge carrier modulation in ferromagnetic semiconductors) 8,9 , magneto-ionic effects (voltage-driven ion motion) 10,11 or strain-mediated multiferroic coupling [12][13][14] , when the magnetic films are grown in direct contact with piezoelectric or ferroelectric underlayers or substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suitable voltages should be selected to achieve maximum reduction in coercivity so that information can be written with low applied magnetic fields (low electric currents and minimizing power dissipation by the Joule heating effect). 78 As flexoelectric effects are inversely proportional to the features' size, i.e., "bits" size, larger effects are anticipated at the nanoscale. This is appealing for high density magnetic recording media.…”
Section: B Strain-graded Me Composites For Energy-efficient Informati...mentioning
confidence: 99%
“…The FE polarization reversal results in the same strain-induced magnetic state at remanence for both the positive and negative voltage branches, which renders this effect unsuitable for non-volatile memory applications. Recent studies have shown that asymmetric polarization curves [27][28] and specific polarization reversal paths related to the FE domain structure [29][30][31][32] provide a possibility to break the symmetry of ME curves in strain coupled heterostructures.…”
Section: Introductionmentioning
confidence: 99%